The Correlation of Learning Motivation with Critical Thinking Skills for Accounting Learning - Lisya Nurlaily Hajar Marfuah; Sunardi Sunardi; Susilaningsih Susilaningsih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The research objective was to examine the correlation between learning motivation and critical thinking skills. This research design was descriptive correlation research with a quantitative approach. Additionally, the research sample consisted of 72 students. The data collection technique used learning motivation questionnaires and a critical thinking ability test. The data were analyzed using Pearson product-moment correlation analysis and a simple regression test assisted by IBM SPSS 20. The results of the correlation test obtained rxy = 0.367. Therefore, it can be interpreted that the correlation category was at a low correlation level. Furthermore, using a simple linear regression test, the researchers got an R-square value = 0.135. It meant that learning motivation contributed 13.5% to critical thinking skills, with a significance through tcount (3,300) > ttable (1,994). The results showed that there was a significant correlation between critical thinking skills with learning motivation.